Keterkaitan Ilmu Fikih dengan Berbagai Bidang Keilmuan : Sebuah Kajian Integratif - Ledian Purnanda (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Fiqh is not a revelation from heaven, but rather the result of ijtihad which is a product of human thought. Therefore, it is important to ask critical questions such as: who defined it, for what purpose, in what social context it was formulated, in which geographical area, and with what epistemological approach. These factors greatly influence the process of forming fiqh. In other words, fiqh was not born in a vacuum, but rather developed along with the course of history and was influenced by the dynamic interaction between thinkers and the socio-cultural and socio-political environment in which they were located. This article uses a literature review methodology to examine the historical and social dynamics in the formation of fiqh. Unfortunately, fiqh that is developing among Muslims today is still heavily influenced by medieval works, especially those from Middle Eastern scholars. This condition shows the need for renewal and reactualization of fiqh according to the context of the contemporary era and society.